Cricklewood Community Play Association presents John B Keane's 'The bodhrán makers', an Irish community play for North and West London - Cricklewood Community Play Association, CCPA (1993)
Printed brochure advertising the forthcoming production, including a description of the play, profiles of key personnel, aims and objectives, anticipated benefits, equal opportunities policy, monitoring / evaluation, timeline flowcharts and legal status. Note: expenditure and income pages are missing from this copy.